Comparative characterization Ukrainian and Russian folk riddles - Щербак, Світлана Валентинівна; Каневська, Ольга Борисівна (Philological Studies: the Scientific Publication of Kryvyi Rih State Pedagogical University, 2012)
In an article comparative aspect analyses Ukrainian and Russian folk riddles, characterized their themed art-shaped features? Indentified their differences and similarities.